HOMESCHOOLING: A FORMULA FOR ESTABLISHING ISLAMIC EDUCATION IN REMOTE COMMUNITIES IN INDONESIA - Hatta Fakhrurrozi; Saepudin Mashuri (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2021)
The disparity in the equality of education in Indonesia, especially in backwoods areas, is one of the problems of education in Indonesia. One of the Government's action in overcoming this gap is by distributing teachers to remote areas of the country. In addition, the government also stipulates several laws and regulations as the formal legality of education in backwoods communities. This study aims to explore the possibility of implementing the homeschool education model (homeschooling) for backwoods communities, as an effort to applied Islamic subject matter and prevail education in Indonesia. This study uses a naturalistic phenomenological approach, using triangulation as one of the data analyzes. The research location is in Hansibong, a backwoods hamlet in the Sojol mountains of ParigiMoutong district, Central Sulawesi. The results of this study found that education in Hansibong is carried out informally within the family. Learning process is held in a traditional way, using very minimal of media, methods and subject matter. The material taught is limited to morality values, reading and writing, arithmetic and the ability to survive in nature. Islamic education in its function as a strengthening of cognitive intelegence, morals, spirituality and nationality has not been provided in learning at home. As a research implication, a homeschooling socialization effort is needed so that the student community can continue to a higher level. The implementation of homeschooling that is not in accordance with the technical guidelines issued by the government will only disserve students because learning outcomes cannot be equalized with existing education levels.